2018
DOI: 10.1016/s2352-4642(18)30031-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water quality, sanitation, hand washing, and nutritional interventions on child development in rural Bangladesh (WASH Benefits Bangladesh): a cluster-randomised controlled trial

Abstract: SummaryBackgroundPoor nutrition and hygiene make children vulnerable to delays in growth and development. We aimed to assess the effects of water quality, sanitation, handwashing, and nutritional interventions individually or in combination on the cognitive, motor, and language development of children in rural Bangladesh.MethodsIn this cluster-randomised controlled trial, we enrolled pregnant women in their first or second trimester from rural villages of Gazipur, Kishoreganj, Mymensingh, and Tangail districts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 55 publications
2
84
1
Order By: Relevance
“…This method of defining risk for delay was used as a conservative strategy because there was no prior research informing a culturally appropriate clinical cut-off in this study population. Binary variables were used to incorporate a quantitative definition of poor development and to be consistent with analyses used in the main WASH Benefits publications [46,58].…”
Section: Early Childhood Developmentmentioning
confidence: 99%
“…This method of defining risk for delay was used as a conservative strategy because there was no prior research informing a culturally appropriate clinical cut-off in this study population. Binary variables were used to incorporate a quantitative definition of poor development and to be consistent with analyses used in the main WASH Benefits publications [46,58].…”
Section: Early Childhood Developmentmentioning
confidence: 99%
“…An estimated 22% or 150 million children younger than 5 years of age are stunted [2]. Even the most optimal food-based interventions have limited effects on preventing or correcting linear growth deficits [5][6][7][8]. Recently, attention has been directed towards environmental enteric dysfunction (EED) as an important component to suboptimal childhood Environmental enteric dysfunction histology index PLOS Neglected Tropical Diseases | https://doi.org/10.1371/journal.pntd.0007975 January 13, 2020 2 / 21…”
Section: Introductionmentioning
confidence: 99%
“… 15 A companion trial in Bangladesh has reported significant effects on growth with improved nutrition, reductions in diarrhoea with improvements in water, sanitation, handwashing, or nutrition, 16 and improvements in indicators of child development across all intervention groups. 17 The objective of the present analysis was to evaluate two hypotheses. First, interventions improving water quality; sanitation; handwashing with soap; water, sanitation, and handwashing in combination; nutrition; or water, sanitation, handwashing, and nutrition in combination would improve indicators of child development during the first 2 years of life.…”
Section: Introductionmentioning
confidence: 99%